Stride parameters in endurance runners - Incalza, P. (New Studies in Athletics, 2007)
It is commonly thought that athletes automatically adapt to a simple, natural and cyclical action, such as running, and that any increases in performance level are almost entirely due to improvements of the conditional capacity and metabolic Systems. The importance of mechanical and coordinative attributes and the possibilities for conserving movement and reutilising elastic energy deriving from the eccentric contraction movements have rarely been explored and have never been a focal point of research in endurance sports. This study included 61 male and female long-distance runners, 31 of whom per-formed at a national/international level and 30 of whom were amateur level competitors. In periodic tests conducted for functional evaluations, video recordings were made of the athletes' running movements at different speeds. Several kinematic parameters were analysed. The statistical results, behavioural analysis and individual adaptations obtained are useful for elaborating and proposing methodological elements in training for correcting and perfecting distance running technique.